Introduction to the philosophy of sport - Reid, Heather L. (Lanham, Maryland : Rowman & Littlefield, 2012)
Introduction to the Philosophy of Sport begins with the history of sport, delves into both the metaphysics and ethics of sport, and also addresses dimensions of the social and political elements of sport. This book is a comprehensive introduction to the philosophy of sport with a straightforward layout that professors can plan and build their courses around.
Introduction: why study the philosophy of sport? -- The ancient hellenic heritage -- The modern olympic revival -- Sport and play -- Sport and games -- Sport and social practices -- Sport and art -- Mind and body -- Consequentialism and play -- Deontology and fairness -- Virtues and vices -- Ethical spectacle -- Sport and education -- Sport and social categories -- Sport and political ideals -- Sport and globalization -- Conclusion: ten intrinsic values of sport.
Includes bibliographical references and index.
Keywords: SPORTS PHILOSOPHY